Nutritional intervention and physical training in malnourished frail community-dwelling elderly persons carried out by trained lay “buddies”: study protocol of a randomized controlled trial - Dorner, Thomas E (BioMed Central, 2013)
BACKGROUND: In elderly persons frailty and malnutrition are very common and can lead to serious health hazards such as increased mortality, morbidity, dependency, institutionalization and a reduced quality of life. In Austria, the prevalence of frailty and malnutrition are increasing steadily and are becoming a challenge for our social system. Physical training and adequate nutrition may improve this situation. METHODS/DESIGN: In this randomized controlled trial, 80 malnourished frail community-dwelling patients (≥ 65 years) hospitalized at wards for internal medicine are recruited. Additionally, 80 lay volunteers (≥ 50 years), named buddies are recruited and subsequently trained regarding health enhancing physical activity and nutrition in four standardized training sessions. These buddies visit the malnourished frail persons at home twice a week for about one hour during an initial period of 10–12 weeks. While participants allocated to the intervention group (n = 40) receive intervention to improve their fluid intake, protein and energy intake, perform strength training and try to increase their baseline activities, the control group (n = 40) only gets home visits without any intervention. After 10–12 weeks, both, the intervention and the control group, receive the nutritional intervention and the physical training. Health, nutritional and frailty status, physical fitness, body composition and chronic inflammation of buddies and frail persons are recorded before the intervention, after 10–12 weeks, 6 and 12 months. DISCUSSION: To your knowledge this trial is the first of its kind to provide nutritional and physical activity interventions to malnourished frail community-dwelling persons by trained lay buddies, in which an improvement of the frail persons´ and the buddies’ health status is measured. This study assesses the efficacy of such an intervention and may offer new perspectives for the management of frailty and malnutrition. TRAIL REGISTRATION: ClinicalTrials.gov, NCT01991639